Aedes albopictus invasion across Africa: the time is now for cross-country collaboration and control. Issue 4 (April 2023) - Longbottom, Joshua; Walekhwa, Abel W; Mwingira, Victor; Kijanga, Oliver; Mramba, Furaha; Lord, Jennifer S
Summary: The distribution of Aedes albopictus across west Africa is well documented. However, little has been done to synthesise data and establish the current distribution of this invasive vector in central and east Africa. In this Viewpoint, we show that A albopictus is establishing across Africa, how this is potentially related to urbanisation, and how establishment poses risks of near-term increases in arbovirus transmission. We then use existing species distribution maps for A albopictus and Aedes aegypti to produce consensus estimates of suitability and make these estimates accessible. Although urban development and increased trade have economic and other societal gains, the resulting potential changes in Aedes -borne virus epidemiology require a discussion of how cross-country collaboration and mitigation could be facilitated. Failure to respond to species invasion could result in increased transmission of Aedes -associated pathogens, including dengue, chikungunya, and Rift Valley fever viruses.